2015
DOI: 10.1093/annhyg/mev022
|View full text |Cite
|
Sign up to set email alerts
|

Eye Lens Opacities Among Physicians Occupationally Exposed to Ionizing Radiation

Abstract: We compared the frequency of lens opacities among physicians with and without occupational exposure to ionizing radiation, and estimated dose-response between cumulative dose and opacities. We conducted ophthalmologic examinations of 21 physicians with occupational exposure to radiation and 16 unexposed physicians. Information on cumulative radiation doses (mean 111 mSv) was based on dosimeter readings recorded in a national database on occupational exposures. Lens changes were evaluated using the Lens Opaciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…This might suggest that the levels of exposure observed in the present study did not significantly influence the development of opacities. This conclusion is in agreement with the outcome of a Finish study [18] in which no association was found at the low exposure level of 111 mSv in average terms.…”
Section: Dose-response Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…This might suggest that the levels of exposure observed in the present study did not significantly influence the development of opacities. This conclusion is in agreement with the outcome of a Finish study [18] in which no association was found at the low exposure level of 111 mSv in average terms.…”
Section: Dose-response Analysissupporting
confidence: 92%
“…Moreover, citing the conclusion of Auvinen [18], these findings do not contradict the results presented in other papers reporting the occupational radiation exposure levels to the eye lens of the ICs and the related increased risk of opacities [19][20][21], as the doses presented are much lower, and also lower than the new dose threshold of 0.5 Gy for detectable opacities. In particular, the cumulative doses assessed in this study are almost 2 times lower than the ones in the French O'CLOC study calculated using a similar approach; 224 mSv in the Polish study vs. 423 mSv in the French study.…”
Section: Dose-response Analysissupporting
confidence: 73%
“…In our study, histological analyses of the eyes of prenatally irradiated animals revealed an intact lens stalk, which has previously been observed in the birth defect termed “congenital lens opacity” in C57BL6/J mice (Smith et al, ). How this defect may relate to other radiation‐induced EDs, such as cataract (Auvinen, Kivelä, Heinävaara, & Mrena, ; Hammer et al, ) (also classified as a “lens opacity”) remains to be elucidated. Of note is that cataract can be congenital in nature as well (Deng & Yuan, ; Pichi, Lembo, Serafino, & Nucci, ), although a link between prenatal radiation exposure and the incidence of this congenital cataract is debatable (Lie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that accommodative capability of the eye depends on an individual's age, the absorbed dose, and duration of IR exposure (Sergienko and Fedirko, 2002); in individuals exposed to various doses of IR, it was found to be reduced in younger patients. However, Auvinen et al (2015) reported that the frequency of lens opacities did not increase in physicians with occupational exposure to IR. Therefore, we studied chromosomal aberrations in cataract patients from a Chinese population occupationally exposed to IR.…”
Section: Discussionmentioning
confidence: 94%